Validation and Characterization of an Srcap Conditional Knockout Mouse - Johal, Karanveer (Université d'Ottawa / University of Ottawa, 2026)
Neurodevelopment requires precise regulation of gene expression, and disruption of chromatin remodeling contributes to neurodevelopmental disorders. SRCAP mediates the deposition of histone variant H2A.Z into the genome. H2A.Z influences gene expression, thus regulating brain development. However, the function of SRCAP in neurodevelopment remains unexplored. Here, we investigated Srcap function using N2A cells and a cortex-specific Srcap knockout (KO) mouse. We found that knockdown of Srcap in N2A cells reduced H2A.Z deposition at candidate genes and disrupted H2A.Z dynamics during neuronal differentiation, thus impairing gene expression. In vivo, conditional deletion of two Srcap alleles resulted in reduced cortical thickness and ventricular and cortical area, as well as impaired progenitor specification and neuronal migration. Notably, mice lacking only one Srcap allele (cHet) exhibited altered anxiety-related and exploratory behaviours. Together, these findings identify Srcap as a critical regulator of cortical development and behaviour by controlling H2A.Z deposition. -- Le développement neurologique nécessite une régulation précise de l'expression génétique, et la perturbation du remodelage de la chromatine contribue aux troubles du neurodéveloppement. SRCAP intervient dans le dépôt de la variante d'histone H2A.Z dans le génome. H2A.Z influence l'expression génétique, régulant ainsi le développement cérébral. Cependant, la fonction de SRCAP dans le développement neurologique reste inexplorée. Nous avons étudié la fonction de Srcap à l'aide de cellules N2A et d'une souris knockout (KO) spécifique du cortex. Nous avons découvert que l'inhibition de Srcap dans les cellules N2A réduisait le dépôt d'H2A.Z au niveau des gènes candidats et perturbait la dynamique d'H2A.Z pendant la différenciation neuronale, altérant ainsi l'expression génique. In vivo, la délétion conditionnelle de deux allèles de Srcap a entraîné une réduction de l'épaisseur corticale et des zones ventriculaires et corticales, ainsi qu'une altération de la spécification des progéniteurs et de la migration neuronale. Il est à noter que les souris ne possédant qu'un seulallèle Srcap (cHet) présentaient des comportements anxieux et exploratories modifiés. Ensemble, ces résultats identifient Srcap comme un régulateur essentiel du développement cortical et du comportement en contrôlant le dépôt de H2A.Z.
Keywords: Histone Variant; Histone Chaperone; H2A.Z; Srcap; Neurodevelopment; Cortical Development; Behaviour